1984
DOI: 10.3109/09638288409166962
|View full text |Cite
|
Sign up to set email alerts
|

State of the art of functional electrical stimulation in France

Abstract: After summarizing the various physiological and functional effects of surface electrical stimulation, the authors review its main applications, including chronic-use or training orthoses, neuromuscular facilitation and automatic cyclical stimulation. Each of the therapeutic principles is illustrated by discussion of an example, with particular emphasis being placed on the practical methods of application that determine the success of the programme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…11 Application of an electrical current to the skin stimulates lower motor nerves and muscle fibres resulting in improved contractility and greater muscle bulk. 12 Decreased spasticity and sensory cortex activation occurs via afferent neuron stimulation, with additional information being provided by the proprioceptive and visual perception of ESinduced joint movement. [13][14][15] Clinical reports have suggested that ES can improve muscle group strength, joint malalignment, muscle tone, sensory deficits, pain-free range of passive humeral lateral rotation (PHLR) and selfreported pain intensity.…”
Section: Introductionmentioning
confidence: 99%
“…11 Application of an electrical current to the skin stimulates lower motor nerves and muscle fibres resulting in improved contractility and greater muscle bulk. 12 Decreased spasticity and sensory cortex activation occurs via afferent neuron stimulation, with additional information being provided by the proprioceptive and visual perception of ESinduced joint movement. [13][14][15] Clinical reports have suggested that ES can improve muscle group strength, joint malalignment, muscle tone, sensory deficits, pain-free range of passive humeral lateral rotation (PHLR) and selfreported pain intensity.…”
Section: Introductionmentioning
confidence: 99%
“…Application of an electrical current to the skin has been shown to stimulate lower motor nerves and muscle fibers, resulting in improved contractility and greater muscle bulk. Importantly, it has also been shown to decrease sensory cortex activation via stimulation of unmyelinated afferent neurons [60]. Clinical reports have suggested that electrical stimulation can improve muscle strength, joint malalignment, muscle tone, sensory deficits, and self-reported pain intensity [61].…”
Section: Surface Electrical Stimulationmentioning
confidence: 99%
“…Peroneal nerve stimulation may suppress ankle clonus in ambulatory hemiplegic patients via reciprocal inhibition (78). Electrical stimulation has limited but defined applications as a dorsiflexor-assist during hemiplegic gait, and as a hand-opening educational device in the plegic upper extremity (79,80).…”
Section: Electrical Stimulationmentioning
confidence: 99%